Cross-cultural adaptation and validation of the infant feeding style questionnaire in Brazil - Pedroso, Jéssica (2021)
We cross-culturally adapted and validated the Infant Feeding Style Questionnaire (IFSQ) in Brazil. The cross-cultural adaptation and content validity assessment was conducted in five steps: translation, synthesis of translations, back-translation, evaluation by experts, and pre-test. To evaluate reliability, construct validity, and floor and ceiling effects, interviews were conducted with 465 mother-infant pairs at Primary Health Centers in the Federal District, Brazil. The mothers answered the Brazilian Portuguese version of the IFSQ (IFSQ-Br), which evaluated four feeding styles (laissez-faire, pressuring, restrictive, and responsive) from 9 sub-constructs. The indulgent style was not evaluated due to time limitation. We performed reliability analysis using Cronbach’s alpha coefficient and construct validity was evaluated through Confirmatory Factor Analysis. Higher means were found in the sub-constructs of the responsive and restrictive styles. The IFSQ-Br presented adequate reliability (α = 0.73) with values for the Cronbach’s alpha coefficient of the sub-constructs ranging from 0.42 to 0.75. In the Confirmatory Factor Analysis, the final models presented good fit, with the Comparative Fit Indices (CFI) ranging from 0.86 to 1.0 and the Root-Mean Squared Error of Approximation (RMSEA) between 0.0 and 0.09. The IFSQ-Br was shown to be a valid and reliable questionnaire to evaluate maternal feeding beliefs and behaviors in Brazil. Future studies should evaluate the psychometric properties of the indulgent style and include mother-infant pairs from different cultural contexts in Brazil.